The Ideal of Environmental Protection as Protected Areas: a literature review - Jeronymo, Carlos André Luz; Silva, Elmo Rodrigues da; Fonseca, Kenny Tanizaki (Ciência e Natura, 2022)
This article analyzes the evolution process of the Protected Areas and the changes in views regarding environmental protection. It is a literature review. In Brazil and other countries, the Protected Areas were created according to international models with different conceptions, mainly the International Union for Conservation of Nature (IUCN) recommendations. In the IUCN International Protected Areas System, specific categories of strict sense protected areas allow natural resources and human occupation. In others not. The debate on this issue remains controversial worldwide. On the one hand, there are preservationists (strict protection believers) who argue that only sites with the objective of strict preservation should have the status of Protected Areas. Conservationists believe that such sites could maintain this status, even though they are not exclusively focused on strict preservation. The historical trend persists in considering land use and access to natural resources in occupying space, emphasizing issues of their domain and management, causing conflicts of views and interests. As a result, the establishment and maintenance of areas to be protected become more complex, mainly when they are historically occupied and used by man.